Qur’anic Psychotherapy: Exploring the Therapeutic Dimensions of the Qur’an in Mental Healing - Ridwan; najwan nafiah nafiah (STAI Al-Mujtama Pamekasan, 2024)
This paper explores the concept of psychotherapy within the Qur’anic framework, emphasizing its therapeutic dimensions in addressing mental and spiritual well-being. The study argues that the Qur’an presents a holistic model of healing that integrates psychological, moral, and spiritual elements. Through a qualitative textual analysis of selected Qur’anic verses, this research identifies key therapeutic mechanisms such as remembrance (dhikr), reflection (tafakkur), reliance on God (tawakkul), and purification of the soul (tazkiyat al-nafs). The findings reveal that the Qur’an not only diagnoses psychological distress—such as anxiety, despair, and inner conflict—but also offers structured methods for healing. These methods operate on multiple levels, including cognitive restructuring, emotional regulation, and spiritual transformation. Furthermore, the study demonstrates that Qur’anic psychotherapy differs fundamentally from secular approaches by grounding mental health in a theocentric worldview. The Qur’an positions ultimate healing as a process of reconnecting the human soul with divine guidance. This study contributes to the growing field of Islamic psychology by providing a systematic framework for understanding Qur’anic approaches to mental health, offering both theoretical insights and practical implications for contemporary psychotherapy.